Buffer Overflow Exploits - Farooq, Khurram; Ugaili, Ayaz (JISR management and social sciences & economics, 2003)
The focus of this Study is on providing an understanding of buffer overflows, the ways they are exploited, and ways to prevent attackers from abusing them. Although this problem has been around for decades, the devastating effects have been downplayed by the commercial organizations due to the fact that they require a lot of effort to trace and to fix. This has led to a flood of software on the market which claims to be secure, yet can be exploited by wily hackers. As our reliance on closed-source and proprietary systems increases, we have to face the facts that there could be a myriad of security vulnerabilities in the very tools we use to protect critical data. To be informed is to be better armed.